2021
DOI: 10.3390/ph14080762
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Significance of Hypermetabolic Lymph Nodes Detected by 2-[18F]FDG PET/CT after COVID-19 Vaccination: A Systematic Review and a Meta-Analysis

Abstract: Recently, several articles reported incidental findings at 2-[18F]FDG PET/CT in patients who have received COVID-19 vaccinations, including hypermetabolic axillary lymph nodes (HALNs) ipsilateral to the COVID-19 vaccine injection site which may cause diagnostic dilemmas. The aim of our work was to calculate the prevalence of this finding. A comprehensive computer literature search of PubMed/MEDLINE, Embase, and Cochrane library databases was performed to identify recently published articles that investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…The current study demonstrates that the overall incidence of any-grade VAHL following the third Covid-19 vaccine dose is basically similar to that reported following the rst and second Covid-19 vaccine doses [8][9][10][14][15][16]. However, VAHL cases following the third dose were found to have shorter duration andlow uptake intensity after the rst 5 days from vaccination.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The current study demonstrates that the overall incidence of any-grade VAHL following the third Covid-19 vaccine dose is basically similar to that reported following the rst and second Covid-19 vaccine doses [8][9][10][14][15][16]. However, VAHL cases following the third dose were found to have shorter duration andlow uptake intensity after the rst 5 days from vaccination.…”
Section: Discussionsupporting
confidence: 76%
“…The characteristics of VAHL following the rst and second vaccine doses were reported to be different [8,10,16]. This probably re ects the difference between the immune response elicited by a rst vaccine dose and the amnestic response induced by a booster given 3 weeks later.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, they also observed that Aβ 1-42 significantly increased SARS-CoV-2 infectivity and that the clearance of Aβ 1-42 can be reduced during SARS-CoV-2 infection [10]. Similar findings with other radiopharmaceuticals were recently described [7][8][9], but this is the first case to show that also [ 18 F]Florbetaben PET/CT can demonstrate immune-induced findings, also amplified by the beta-amyloid presence, associated with the current COVID-19 pandemic vaccination programs, being a potential finding on whole-body protocols for the assessment of cardiac/systemic amyloidosis.…”
Section: Case Presentationsupporting
confidence: 77%
“…We assume that the subcutaneous and the potential lymph node uptake might be related to an induced inflammation with peptides deposition, as amyloid-beta peptides are involved in the systemic inflammatory process such as in the physiopathology of AD, and chronic, low-level systemic inflammation may exacerbate the Aβ deposition [3][4][5][6]. Such induced inflammation, already demonstrated with several tracers [7][8][9], may be further enhanced in AD patients by the amyloid-beta presence. In this sense, Hsu et al observed in a preclinical study that the intracellular immunoreactivity was significantly increased by the SARS-CoV-2 pseudovirus in the presence of Aβ 1-42 (a strong indicator of AD with high affinity for SARS-CoV-2 spike protein S1 subunit) compared to SARS-CoV-2 pseudovirus alone.…”
Section: Case Presentationmentioning
confidence: 87%
“…VAHL, vaccine-associated hypermetabolic lymphadenopathy; BMI, body mass index. Active malignancy, this variable was considered positive in cases of treatment-naïve patients, those who received recent anti-cancer therapy, and those with recurrent disease identified on their [ 18 [14][15][16]. However, VAHL cases following the third dose were found to have shorter duration and low uptake intensity after the first 5 days from vaccination.…”
Section: Discussionmentioning
confidence: 99%